Architecture : A Very Short Introduction - Ballantyne, Andrew (New York Oxford University Press, 2002)
This guide intends to help us understand the cultural significance of the buildings that surround us. It avoids the traditional style-spotting approach in favour of giving an idea of what it is about buildings that moves us.
Include Index and Illustration
Keywords: Architecture -- Bouwkunst